Phytophthora species causing root rot in avocado seedlings at Colombian nurseries: Morphological, molecular, and pathogenic analysis (Scientia Agropecuaria, 2025)
Expansion of avocado production areas in Colombia has led to an increased demand for plant propagation material. However, this expansion has exacerbated phytosanitary challenges, particularly root rot disease mainly associated with Phytophthora spp. Therefore, this study aimed to identify Phytophthora species associated with root rot in avocado seedlings within nurseries. Avocado plants exhibiting wilting symptoms were collected from nurseries in the departments of Quindío, Risaralda, and Valle del Cauca (Colombia). Segments of diseased roots were selected, cut, and surface-disinfected, before being planted on Potato Dextrose Agar (PDA) supplemented with antibiotics and fungicides. Microorganism identification was conducted using taxonomic keys and confirmed by molecular techniques employing the identification based on phylogenetic hypothesis, using ITS1-5.8s-ITS2 region encoding for rRNA. Isolates obtained from necrotic avocado roots were identified as P. cinnamomi and P. heveae. The pathogenicity of the isolates was confirmed in avocado seedlings through inoculation, resulting in symptom reproduction. Consequently, this study identified P. cinnamomi and P. heveae as causal agents of root rot in avocado during the nursery stage.